MENGUKUR DAN MERANCANG MODEL KETAHANAN ENERGI MELALUI PERUBAHAN PERILAKU KONSUMEN ENERGI TERBARUKAN - Nufian S Febriani; Fitria Avicenna (Fakultas Seni Rupa dan Desain ITB, 2021)
The benefits of renewable energy in Indonesia are not well understood by consumers. This research suggests the use of renewable energy, which is very beneficial for consumers. This research also has implications for policy makers, electricity suppliers, and future researchers. Using two online and offline survey methods, this study can formulate a behavior change model that can help policy makers identify marketing and branding strategies so that they are expected to succeed in changing consumer behavior and increasing the degree of consumer involvement in renewable energy products, for example in forming an energy independent community. Therefore, in addition to strengthening the use of renewable energy, other sections such as marketing and further research on consumer behavior must continue to be carried out in order to obtain a whole independent energy system.